2010
DOI: 10.1007/s12149-010-0375-9
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with 18F-fluoroethylcholine PET/CT in staging and monitoring therapy response of advanced renal cell carcinoma

Abstract: In this small sample more than half of the RCC metastases were evident in baseline FEC PET. Monitoring therapy, FEC PET showed heterogeneous results in the first case with PD and was consistent with ceCT in the second one displaying PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The ease, relative low cost, noninvasive and high sensitivity of BLI allow rapid screening of large chemical libraries in very small quantities and subsequent SAR studies. Currently, human PET/CT imaging has been used to monitor tumor progression, evaluation, and response to therapy (44-46). PET imaging has also been used for pre-clinical studies for evaluation of the efficacy of different HDACi in small animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The ease, relative low cost, noninvasive and high sensitivity of BLI allow rapid screening of large chemical libraries in very small quantities and subsequent SAR studies. Currently, human PET/CT imaging has been used to monitor tumor progression, evaluation, and response to therapy (44-46). PET imaging has also been used for pre-clinical studies for evaluation of the efficacy of different HDACi in small animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Horn et al compared 18 F-FLT and 18 F-FDG for early measurement of response to sunitinib treatment in 20 patients with metastatic RCC and demonstrated that while FLT-PET could be used to identify response as early as 1 week after the start of treatment, 18 F-FDG PET was more effective at a later time point of 3–4 weeks, suggesting that inhibition of VEGF signaling with sunitinib exerts an early effect on tumor proliferation, which is then followed by a reduction in tumor metabolism [24]. Two groups have reported the utility of 18 F-fluoroethylcholine PET [25] and 11 C-acetate PET [26] for staging and monitoring of the response of advanced RCC to therapy. Furthermore, one preliminary report has demonstrated that anti-3- 18 F-FACBC PET showed better conspicuity for papillary RCC than for clear cell RCC [27].…”
Section: Kidney Cancermentioning
confidence: 99%
“…44 Other novel PET radiotracers To date, several other novel radiotracers have been evaluated for RCC imaging. These include anti-1-amino-3-18 Ffluorocyclobutane-1-carboxylic acid (anti-18 F-FACBC), 46 18 F-fluoroethylcholine, 47 and 18 F-fluoromisonidazole ( 18 F-FMISO). 48 Similar to the case of 89 Zr-bevacizumab and small molecules against PSMA, these tracers have been studied in only a handful of patients and their role in imaging the indeterminate renal mass remains in question.…”
Section: Zr-bevacizumabmentioning
confidence: 99%